Wages and international factors' mobility - Elena Podrecca; Gianpaolo Rossini (Alma Mater Studiorum - Università di Bologna, Dipartimento di Scienze Economiche (DSE), 2012)
The labor wage is the result of market variables and institutional settings of a country. In an open economy the determination of the market wage rate may be further affected by the extent of international mobility of both factors of production, labor and capital. Labor mobility is represented by migration in and out of a country, while capital mobility relates mostly to the extent of foreign direct investment (FDI) outflows and inflows. Migrants may represent an addition to the native labor force of a country and, in some cases, play a substitute role with respect to incumbent workers. FDI, in particular of the greenfield category, represents either a supplement to or a reduction of the domestic capital and, by and large, changes the opportunity set of a firm's CEO with respect to the corresponding company operating in a closed economy. International factor mobility and domestic market variables, such as unemployment and productivity, interact in the wage setting process. In this paper, we derive a theoretical wage equation following the above premises, and perform pooled mean group estimates of its parameters on panel data for a group of 13 European countries with quarterly time observation over the period 1996-2007. We find that capital outflows have a robust negative effect on the wage rate. The effects of migration inflows, on the other hand, are not so clear-cut, as they can be nullor negative depending on the sample of countries considered.
Keywords: F2; J5; J6; 330